Joint analyses of human milk fatty acids, phospholipids, and choline in association with cognition and temperament traits during the first 6 months of life - Li, Tengfei; Samuel, Tinu M.; Zhu, Ziliang; Howell, Brittany; Cho, Seoyoon; Baluyot, Kristine; Hazlett, Heather; Elison, Jed T.; Wu, Di; Hauser, Jonas; Sprenger, Norbert; Zhu, Hongtu; et al. (Frontiers in Nutrition, 2022)
Early dietary exposure via human milk nutrients offers a window of opportunity to support cognitive and temperamental development. While studies have focused on associations of few pre-selected human milk nutrients with cognition and temperament, it is highly plausible that human milk nutrients synergistically and jointly support cognitive and behavioral development in early life. We aimed to discern the combined associations of a wide array of human milk nutrients with cognition and temperament during the first six months of life and explore if there were persistent effects up to 18 months old, when human milk is the primary source of an infant’s nutrition. The Mullen Scales of Early Learning and Infant Behavior Questionnaires-Revised were used to assess cognition and temperament, respectively, of fifty-four exclusively/predominantly breastfed infants in the first 6 months of life, whose follow-ups were conducted at 6-9, 9-12 and 12-18 months old. Human milk samples were obtained from the mothers of the participants at less than 6 months of life and analyzed for fatty acids (total monounsaturated fatty acids, polyunsaturated fatty acid, total saturated fatty acid (TSFA), arachidonic acid (ARA), docosahexaenoic acid (DHA), ARA/DHA, omega-6/omega-3 polyunsaturated fatty acids ratio (n-6/n-3)), phospholipids (phosphatidylcholine, phosphatidylethanolamine (PE), phosphatidylinositol (PI), sphingomyelin) and choline (free choline, phosphocholine (PCho), glycerophosphocholine). Feature selection was performed to select nutrients associated with cognition and temperament, respectively. The combined effects of selected nutrients were analyzed using multiple regression. A positive association between the arachidonic acid (ARA) and surgency was observed (p = 0.024). Significant effect of DHA, n-6/n-3, PE and TSFA concentrations on receptive language (R2 = 0.39, p = 0.025), and the elevated ARA, PCho, and PI with increased surgency (R2 = 0.43, p = 0.003) was identified, suggesting that DHA and ARA may have distinct roles for temperament and language functions. Furthermore, the exploratory association analyses suggest that the effects of human milk nutrients on R.L. and surgency may persist beyond the first 6 months of life, particularly surgency at 12-18 months (p = 0.002). Our studies highlighted that various human milk nutrients work together to support the development of cognition and temperament traits during early infancy.